Strategy of Muhammadiyah 1 Pandaan Vocational School in Learning Activities in the midst of the Covid-19 Pandemic - Muhlasin Amrullah; Cyesar Melati Merta Putri (Proceedings of The ICECRS, 2021)
This scientific works was created with a purpose, to describe the learning strategis of Vocational High School of Muhammadiyah 1 Pandaan during the Covid pandemic. In this research process to get the data using techniques by interview, observation and also the voice recording when the research process was carried out. Vocational High School of Muhammadiyah 1 Pandaan use daring (online learning) for strategies during pandemic Covid-19, as for several supporting apllications used like Youtube, Zoom Meeting, Google Classroom ,ect. In the implementation of a strategy Vocational High School of Muhammadiyah 1 Pandaan have some obtacles, but even so Vocational High School of Muhammadiyah 1 Pandaan keep to develop the learning strategy, so that online learning goes well.